Scheduling Project Crashing Time Using Linear Programming Approach: Case Study - K. Chitra (International Journal of Research in Industrial Engineering, 2017)
In today’s competitive environment completing a project within time and budget, is very challenging task for the project managers. This aim of this study is to develop a model that finds a proper trade-off between time and cost to expedite the execution process. Critical path method (CPM) is used to determine the longest duration and cost required for completing the project and then the time-cost trade–off problem (TCTP) is formulated as a linear programming model. Here, LINDO program is used to determine the solution of the model. To implement the proposed model, necessary data were collected through interviews and direct discussion with the project managers of Chowdhury Construction Company, Dhaka, Bangladesh. The analysis reveals that through proper scheduling of all activities, the project can be completed within 120 days from estimated duration of 140 days. Reduction of project duration by 17% is achieved by increasing cost by 3.73%, which is satisfactory.